ChemInform Abstract: Iridium‐Catalyzed Dynamic Kinetic Isomerization: Expedient Synthesis of Carbohydrates from Achmatowicz Rearrangement Products. Issue 44 (15th October 2015) - Wang, Hao‐Yuan; Yang, Ka; Bennett, Scott R.; Guo, Sheng‐rong; Tang, Weiping
Abstract A highly stereoselective dynamic kinetic isomerization of Achmatowicz rearrangement products is presented.